2020
DOI: 10.1111/tri.13582
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor lung quality on post‐transplant recipient outcome in the Lung Allocation Score era in Eurotransplant – a historical prospective study

Abstract: The aim of this study was to investigate whether there is an impact of donation rates on the quality of lungs used for transplantation and whether donor lung quality affects post-transplant outcome in the current Lung Allocation Score era. All consecutive adult LTx performed in Eurotransplant (ET) between January 2012 and December 2016 were included (N = 3053). Donors used for LTx in countries with high donation rate were younger (42% vs. 33% ≤45 years, P < 0.0001), were less often smokers (35% vs. 46%, P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although the absolute numbers of death on the waitlist increased, so did the total amount of transplants. The increase in the number of transplantations may be attributed to more frequent acceptation of donor lungs with extended criteria within the Eurotransplant region as shown by Smits et al (25). As a result of more transplantations the percentage waitlist mortality did not change.…”
Section: Discussionmentioning
confidence: 92%
“…Although the absolute numbers of death on the waitlist increased, so did the total amount of transplants. The increase in the number of transplantations may be attributed to more frequent acceptation of donor lungs with extended criteria within the Eurotransplant region as shown by Smits et al (25). As a result of more transplantations the percentage waitlist mortality did not change.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a recent study showed that the use of extended criteria organ donors has increased in the Eurotransplant region over the years and that this was associated with shorter survival after transplantation. 17 Given these findings, the absence of a decrease in overall posttransplantation survival could actually represent a beneficial effect of the introduction of the LAS. It is important to note that an improved overall survival was never the goal of the LAS.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the 2018 figures of lung donor utilisation rate were significantly higher in Austria and Belgium (9.8 and 10.8 ppm) where they have opt-out systems for organ donation, compared to Germany and the Netherlands (3.8 and 4.7 ppm) where an opt-in system remains [36]. The waiting list mortality rates in countries with high donation rates are lower compared to those in countries with low donation rates (7% vs. 12% at 1 year), with higher quality donor lungs more often used in these countries with high donation rates, thus offering a chance of better outcomes in recipients [37].…”
Section: Donorsmentioning
confidence: 99%